Evaluation of Diabetes mellitus Patient Care by Determining HemoglobinA1c Level at Chumpolburi Hospital in Surin Province - ฮิมหมั่นงาน, รัตนาภรณ์; ดียิ่ง, จเด็ด; วงศ์ทิมากร, วิไลวรรณ; อาภาสุวรรณกุล, นัยนา (Disease Control Journal, 2008)
This was cross-sectional descriptive study for evaluation of Diabetes mellitus(DM) patient care, who had been attending the Out Patient Department of Chumpolburi hospital, Surin province, during the calendar year 2006. To obtain the efficacy of DM patient care, the determination of blood hemoglobinA1c level in 120 DM patients were done. The other relevant data were collected by interviewing. The prevalence of DM patients with higher hemoglobinA1c level than normal (>7 mole%) had been analyzed along with those factors. The results showed that 50.8 % of DM patients had higher hemoglobinA1c than normal (>7 mole%) and 49.2 % had hemoglobin A1c within normal value control (< 7 mole%). There were no relation between level hemoglobinA1c and gender, age, occupation, marriage status, educational, weight, body mass index, duration of Diabetes Mellitus sickness, self behavior. But patients who got Diabetes Mellitus more than 10 years had better result for treatment, (33% and 17.6%). There were no correlation between self behavior and controlling hemoglobin A1c level. The benefit and application from the study was that the doctors and health care team should pay attention in long term DM patients, complication of the uncontrolled patients and planning further study to cover the affected population of which more information of the factor effects to blood hemoglobinA1c would be pursued.